Simultaneous Detection and Differentiation of Human Rhino- and Enteroviruses in Clinical Specimens by Real-Time PCR with Locked Nucleic Acid Probes - Österback R; Tevaluoto T; Ylinen T; Peltola V; Susi P; Hyypiä T; Waris M (ASM, 2022)
Abstract
Human rhinoviruses (HRVs) and human enteroviruses (HEVs) are significant respiratory pathogens. While HRV infections are restricted to the respiratory tract, HEV infections may spread to secondary target organs. The method of choice for sensitive specific detection of these viruses is reverse transcription (RT)-PCR with primers targeting the conserved 5' noncoding region of the viral RNA. On the other hand, sequence similarities between HRVs and HEVs complicate their differential detection. In this study, we describe the use of locked nucleic acid (LNA) analogues in short double-dye probes which contained only two selectively HRV- or HEV-specific bases. The double-stranded DNA dye BOXTO (4-[6-(benzoxazole-2-yl-(3-methyl-)-2,3-dihydro-(benzo-1,3-thiazole)-2-methylidene)]-1-methyl-quinolinium chloride) was used with the LNA probes in a tricolor real-time PCR assay to allow specific detection of HRVs (probes labeled with 6-carboxyfluorescein [FAM] [green]) and HEVs (Cy5 [red]) with additional melting curve analysis (BOXTO [yellow]). The functionality of the probes was validated in PCR and RT-PCR assays using plasmids containing viral cDNA, quantified viral RNA transcripts, cultivated rhino- and enterovirus prototypes, and clinical specimens. Of 100 HRV and 63 HEV prototypes, the probes correctly identified all HEVs except one that produced only a BOXTO signal. Among 118 clinical specimens with sequencing results, concordant results were obtained for 116 specimens. Two specimens were reactive with both probes, but sequencing yielded only a single virus. Real-time PCR with LNA probes allowed sensitive group-specific identification of HRVs and HEVs and would enable relative copy number determination. The assay is suitable for rapid and accurate differential detection of HRVs and HEVs in a diagnostic laboratory setting.